A Management Algorithm for Stomach Pain in Family Practice: One Result of the ‘Seminartage Weiterbildung Allgemeinmedizin’ (SemiWAM®) Ein Algorithmus zum Umgang mit Bauchschmerz in der Hausarztpraxis: Ein Ergebnis der Seminartage Weiterbildung Allgemeinmedizin (SemiWAM®) - Schneider, Dagmar; Simmenroth, Anne; Roos, Marco (Zeitschrift für Allgemeinmedizin, 2021)
Since 2014 the ‘Koordinierungsstelle Allgemeinmedizin (KoStA)’ has performed one-day courses- called SemiWAM®- for postgraduate education. The topics of the courses follow a five-year curriculum, which is linked to the Competence-Based Curriculum Family Practice of DEGAM (German College of General Practitioners and Family Physicians). From 2017 on, the ‘Kompetenzzentrum Weiterbildung Allgemeinmedizin Bayern (KWAB)’, a Bavarian residency training scheme, provides the SemiWAM®. This paper reports the teaching concept and shows the working result of the course “Stomach pain as a reason for consulting a doctor” in 2016. Participants developed a clinical guideline how to manage patients with stomach pain in family practice. Participants evaluated the course with high grades in matters of practical feasibility. This contribution should foster the discussion on postgraduate education.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Family medicine; General practice; Management; Postgraduate education; Stomach pain